Murder Most Queer The Homicidal Homosexual in the American Theater - Schildcrout, Jordan (University of Michigan Press, 2014)
The "villainous homosexual" has long stalked America's cultural imagination, most explicitly in the figure of the queer murderer, a character in dozens of plays. But as society's understanding of homosexuality has changed, so has the significance of these controversial characters, especially when employed by LGBT theater artists themselves to explore darker fears and desires. Murder Most Queer examines the shifting meanings of murderous LGBT characters in American theater over a century, showing how these representations wrestle with and ultimately subvert notions of gay villainy.